Analysis of the Effect of Min–Max Stock Level (MMSL) Implementation on the Efficiency of Slow-Moving Drug Management: Min–Max Stock Levels in Slow-Moving Drug Control - Amellia Ahmed; Ratna Wardani; Joko Prasetyo (CV. Paperhome Indonesia, 2026)
Background: The management of slow moving drugs in hospital pharmacy installations often faces problems in the form of overstock, high inventory values, increased risk of expiration, and low inventory turnover. This study aims to analyze the effect of the application of Min-Max Stock Level (MMSL) on the efficiency of slow moving drug management in the Pharmaceutical Installation of General Hospital Muslimat Ponorogo which is measured through inventory value, expiration rate, storage cost, and inventory turnover. Methods: Quantitative research design of the case control approach. MMSL implementation independent variables (before and after implementation). Dependent variables are inventory value, drug expiration value, storage cost, and turnover ratio (TOR). Data analysis was carried out descriptively and inferentially using the Mann-Whitney U test for variables that are not normally distributed and independent t-test for the TOR variable that is normally distributed. Result: The results of the analysis showed that in the inventory value variable, Mann-Whitney U = 90,000, Z = –0.933, and p = 0.351 (>0.05), so that there was no significant effect of the application of MMSL on the inventory value. In the storage cost variable, identical results were obtained (U = 90,000; Z = –0.933; p = 0.351), which also showed no significant differences between groups. Meanwhile, the expiration value variable showed a very significant difference with U = 17,500, Z = –4,015, and p < 0.001, which means that there is a significant influence of the application of MMSL on the decrease in the value of losses due to expired drugs. For the variable turnover ratio (TOR), the results of the independent t-test showed p = 0.136 (>0.05), so there was no significant effect of the application of MMSL on TOR. Conclusion: The implementation of MMSL significantly reduces losses due to expired drugs but does not significantly affect inventory value, storage costs, or turnover ratio.